Increased Vascular Permeability Due to Spread and Invasion of Vibrio vulnificus in the Wound Infection Exacerbates Potentially Fatal Necrotizing Disease - Yamazaki, Kohei; Kashimoto, Takashige; Kado, Takehiro; Yoshioka, Kazuki; Ueno, Shunji (Frontiers in Microbiology, 2022)
Vibrio vulnificus is known to cause necrotizing soft tissue infections (NSTIs). However, the pathogenic mechanism causing cellulitis, necrotizing fasciitis, muscle necrosis, and rapidly developing septicemia in humans have not been fully elucidated. Here, we report a multilayer analysis of tissue damage after subcutaneous bacterial inoculation as a murine model of V. vulnificus NSTIs. Our histopathological examination showed the progression of cellulitis, necrotizing fasciitis, and muscle necrosis worsening as the infection penetrated deeper into the muscle tissue layers. The increase in vascular permeability was the primary cause of the swelling and congestion, which are acute signs of inflammation in soft tissue and characteristic of human NSTIs. Most importantly, our sequential analysis revealed for the first time that V. vulnificus not only spreads along the skin and subcutaneous tissues or fascia but also invades deeper muscle tissues beyond the fascia as the crucial process of its lethality. Also, increased vascular permeability enabled V. vulnificus to proliferate in muscle tissue and enter the systemic circulation, escalating the bacterium’s lethality. Our finding may yield important clinical benefits to patients by helping physicians understand the impact of surgical debridement on the patient’s quality of life. Furthermore, this study provides a promising system to accelerate studies of virulence factors and eventually help establish new therapies.